A brief analysis of the “Administrative Responsibility of Legal Persons” regulated in Law Nº. 30424: Entrevista al Dr. Bernardo Feijóo Sánchez - Rodríguez Castro, Carolina (2019)
On April 1, 2016, Law N° 30424 was published in the Official Peruvian newspaper “El Peruano”, which regulates the administrative responsibility of legal entities that later on July 11, 2018 was modified by Law No. 30835, which widens the crimes foreseen by the first Law.The interview has the purpose of giving a general panorama on the matter, through a brief analysis on the norm made by the Spanish Bernardo Feijoo Sánchez.